Damage Identification of Truss Structures Based on Force Method (Advances in Applied Mathematics and Mechanics, 2018)
An computationally efficient damage identification technique for the planarand space truss structures is presented based on the force method and the micro geneticalgorithm. For this purpose, the general equilibrium equations and the kinematicrelations in which the reaction forces and the displacements at nodes are take into account,respectively, are formulated. The compatibility equations in terms of forces areexplicitly presented using the singular value decomposition (SVD) technique. Thengoverning equations with unknown reaction forces and initial elongations are derived.Next, the micro genetic algorithm (MGA) is used to properly identify the site and extentof multiple damage cases in truss structures. In order to verify the accuracy andthe superiority of the proposed damage detection technique, the numerical solutionsare presented for the planar and space truss models. The numerical results indicatethat the combination of the force method and the MGA can provide a reliable tool toaccurately and efficiently identify the multiple damages of the truss structures.